Special sequences in weighted graphs. (2017) - Mathew, Jill K.; Mathew, Sunil
In a weighted graph, the edges are mainly classified into α, β and δ. In this paper, some sequences in weighted graphs are introduced. These concepts are based on the above classification. Characterisations of partial blocks and partial trees are obtained. It is shown that sequence of a partial tree is the zero sequence, and sequence of a partial block is a binary sequence.